ORKESTRASI AL-QUR’AN DALAM MEMULIAKAN ORANG MISKIN DAN MEMUSUHI MENTAL MISKIN: STUDI TEMATIK - A. Muh. Nur Syahid Mappaladeng; Achmad Abubakar; Sohrah Sohrah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Contradictions often arise in Islamic discourse regarding poverty : (1) the honoring of the poor; and (2) an anti-poverty mindset that emphasizes work ethic and self-reliance. This study aims to explore wether the Qur'an teaches both concepts simultaneously and how they harmonize. The research employs the thematic exegesis method (al-tafsir al mawdui). Verses concerning poverty, the rights of the poor, and work ethic were collected and analyzed with reference to prominent exegetical works such as Tafsir al-Tabari, Ibn Kathir, al-Qurtubi, al Maraghi, al-Misbah, and Taysir al-Karim al- rahman, The findings indicate that the Qur'an does not set these two messages in opposition; rather, it integrates them within a framework of balance (tawazun). Honoring the poor is mandated as a matter of structural social justice, while work ethic and the aversion to becominga burden on others are taught as aspects of personal dignity. This harmony resembles an orchestra that blends collective responsibility with individual responsibility. poverty alleviation in Islam must be holistic. Keywords : poverty; poverty mentality; thematic interpretation, orchestration, work ethic